Smart alliance : how a global corporation and environmental activists transformed a tarnished brand - Taylor, J. Gary (Yale agrarian studies., 2004)
Toward the end of the eighteenth century, a radical change occurred in notions of self and personal identity. This was a sudden transformation, says Dror Wahrman, and nothing short of a revolution in the understanding of selfhood and of identity categories including race, gender, and class. In this pathbreaking book, he offers a fundamentally new interpretation of this critical turning point in Western history. Wahrman demonstrates this transformation with a fascinating variety of cultural evidence from eighteenth-century England, from theatre to beekeeping, fashion to philosophy, art to travel and translations of the classics. He discusses notions of self in the earlier 1700s - what he terms the 'ancien regime of identity' - that seem bizarre, even incomprehensible, to present-day readers. He then examines how this peculiar world came to an abrupt end, and the far-reaching consequences of that change. This unrecognised cultural revolution, the author argues, set the scene for the array of new departures that signaled the onset of Western modernity.